1988
DOI: 10.1007/bf01648355
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable mesh in the treatment of rectal prolapse

Abstract: Transabdominal rectopexy is a widely used method with excellent results in the treatment of rectal prolapse; a variety of absorbable and non-absorbable materials has been described in the literature. In the Department of Surgery in the University of Munster we have been using absorbable mesh (Vicryl/Dexon) routinely to perform rectopexy. These materials are practically identical in their mode of degradation. Both are absorbed completely, releasing glycolic acid which is believed to be bacteriostatic. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…These results have been reproduced by others. 35,[44][45][46] The mortality and recurrence rates are similar to figures reported after placement of nonabsorbable meshes.…”
Section: Prosthetic or Mesh Rectopexysupporting
confidence: 78%
See 2 more Smart Citations
“…These results have been reproduced by others. 35,[44][45][46] The mortality and recurrence rates are similar to figures reported after placement of nonabsorbable meshes.…”
Section: Prosthetic or Mesh Rectopexysupporting
confidence: 78%
“…10,16,22,29,31,34,38 Although the sponge rectopexy was popular before 1980, it has lost popularity and is confined to studies before 1994. Other nonabsorbable synthetic meshes have replaced the sponge, and more re- [35][36][37]44 have shown that the use of both absorbable and nonabsorbable meshes achieved similar results. The mortality rate was 0% to 1% and the recurrence rates were 0% to 6% for both absorbable [35][36][37] and nonabsorbable 7,10,13,32,34,37,38 meshes.…”
Section: Prosthetic or Mesh Rectopexymentioning
confidence: 91%
See 1 more Smart Citation
“…In the studied group, recurrences were reported in 37,5% of the patients from 3 to 72 months after the operation (mean 37 months). Arndt and Pircher report recur-rence rate of 6% in the group of 62 patients, 36 to 45 months postoperatively (1).…”
Section: Discussionmentioning
confidence: 99%
“…The time of degradation of the polyglycolic acid or plygalactine meshes is of about 90 days, which is believed to be long enough for appropriate adhesion of the rectum to presacral fascia (1,11). Glycol acid release during degradation may also have bacteriostatic properties (6).…”
Section: Discussionmentioning
confidence: 99%